Plan de negocio para el taller chapista Ariel en mecánica. - Tituaña Canchig, Estefanía Maribel (2019)
This entrepreneurship project seeks to demonstrate the feasibility of a business plan for Taller Chapista Ariel in the city of Quito, with the objective of covering the existing unmet demand in the southern sector of the city, as well as offering the investor a comprehensive project with the possibility of venturing into such a business. Through a market study, the collection of data, the tabulation and the analysis of information is intended to determine how feasible the project is. The applied research methods are analytical-synthetic and inductive-deductive, with the application of techniques such as the survey where the questionnaire was used as an instrument, allowing through this to determine the market segment to be covered, all this by means of an automotive service, based on strategies that allow the positioning of the mechanical workshop at the level of the province of Pichincha. As conclusions it was obtained that the place chosen for the project is important, through the field study it was obtained that a good sector is Guajalo, a place where the workshop will satisfy the needs of the unsatisfied demand and will provide better attention than the competition. It was also determined that the investment of the project that must be incurred for its execution is high, but thanks to the fact that the country, through the state bank, is financing projects for micro-entrepreneurs at a low interest rate, the project is feasible, obtaining from the financial study that 20% of the total investment ($ 27,743.76) would be provided by the owner and 80% of the remaining investment ($ 27,743.76). $ 110,975.05) will be financed through a loan managed in BanEcuador for the purchase of fixed assets, payment of deferred assets and working capital. The equilibrium point calculation concluded that generating a monthly income above $ 7,628.65 approximately will generate profits, the project's MARR was established at 10.73%, the IRR at 55% and a NPV of $ 225,893.37, data that allows credit credibility with the financial entity and security for the owner for its investment, which is expected to be recovered a period of time of 2 years, 9 months and 13 days, with a benefit cost of $ 1.92 for every dollar invested. The venture is viable in its entirety.